Solar cell based power-bank prototype as a media to increase students' scientific literacy - Mayub, Afrizal; Delima, Ega Marita; Nursa’adah, Euis; Fahmizal, Fahmizal; Lazfihma, Lazfihma (Institute of Advanced Engineering and Science, 2024)
This research aims to i) implement the solar cell based power-bank prototype for learning media; ii) describe the feasibility of the solar cell-based power-bank prototype for learning; and iii) describe students' scientific literacy. This research method uses the analysis, design, development, implementation, and evaluation (ADDIE) research and development model. The subjects of this research are class IX students and science teachers at SMPN 4 Central Bengkulu. Data collection techniques include questionnaires, tests, and interviews. The data analysis technique uses N-gain analysis, percentages, and the Aiken's V formula. The research results show that the media developed is valid with an Aiken index value of 0.98 > the minimum standard Aiken' V of 0.92 and can increase students' scientific literacy based on an N-gain of 0.92. 0.71, this can be seen in the dimensions of context and content based on N-gain of 0.73 and 0.69, while the dimensions of attitude, curiosity, respect, and willingness, reflect the respective percentages of 79.62%, 78.86%, 78.89%, 75.60%. Based on the results of the hypothesis test, the sig value is obtained. (2 tailed) 0.000 < 0.05 which means Ha is accepted and Ho is rejected, which means the solar cell-based renewable energy media used in science learning influences the increase in students' scientific literacy.